A terahertz graphene-metamaterial sensor for highly sensitive detection of trace pesticide metaldehyde - Dazhi Zhang; Xinlei Ruan; Maosheng Yang; Honglai Liu; Xiaobing Li; Peipei Li (PLoS ONE, 2025)
To address the demand for rapid detection of trace metaldehyde pesticide residues in agricultural products such as Dendrobium officinale Kimura et Migo (D. officinale), this paper proposes and validates a high-sensitivity metal-graphene hybrid metamaterial sensor, which exhibits significant advantages in the field of pesticide residue detection. The sensor consists of a quartz substrate, periodic gold array, polyimide (PI) spacer layer, and few-layer graphene, and is fabricated using standard micro-nano processing technologies. Utilizing a terahertz time-domain spectroscopy (THz-TDS) system, the reflection spectra of the sensor in response to metaldehyde solutions with different concentrations (0–2400 pg mL -1 ) were measured in the 0.6–1.5 THz frequency band. The results indicate that compared with the bare metamaterial, the introduction of graphene significantly enhances the sensor’s sensitivity, and its resonance intensity decreases noticeably with the increase in metaldehyde concentration. Simulation analyses reveal the existence of the toroidal dipole resonance mode and the mechanism by which the graphene layer induces a resonant red shift by increasing the effective capacitance, while confirming that the regulation of graphene’s Fermi energy level can dynamically modulate the resonance intensity. Experimental measurements show that the hybrid metamaterial sensor achieves a minimum detection limit of 100 pg mL -1 for metaldehyde, with a rapid response in the low concentration range (0–200 pg mL -1 ). This high sensitivity is primarily attributed to the effective modulation of the dielectric environment on the graphene surface by the monolayer adsorption of analytes at low concentrations. The sensor developed in this study exhibits excellent performance, providing an effective technical solution for the rapid screening of pesticide residues in the safety inspection of agricultural products such as D. officinale.